Estimation of seismic attenuation and prediction of VTI anisotropy parameters from VSP and log data: a case study from the Middle East - Alasbali, A.; Pevzner, Roman; Tertyshnikov, Konstantin; Bóna, Andrej; Gurevich, Boris (Springer, 2016)
© 2016, Saudi Society for Geosciences. Quantitative interpretation of seismic data depends upon the amplitude analysis of reflected waves. However, the quality of the image obtained can be significantly affected by attenuation and anisotropy in the overburden. Therefore, the insights into the magnitude, sources and spatial distribution of these parameters may prove to be substantial for improving the quality of seismic image and reservoir characterisation. Both seismic vertical transverse isotropy (VTI) anisotropy and scattering attenuation could be caused by the layering. In order for these phenomena to play a major role, strong elastic contrasts between them are needed. In this paper, we present the case study from a typical setting in the Middle East where such a contrast between stiff carbonates and relatively soft siliciclastic sediments significantly deteriorates the quality of the seismic image. Vertical seismic profiling (VSP) and log data from one of the wells in the region are used to demonstrate this phenomenon. Apparent attenuation from VSP data is estimated using a modified centroid frequency shift method. The log data for seismic forward modelling is used in order to show that scattering could be a significant contributor to the apparent attenuation. In addition, by using both Backus averaging and synthetic walk-away VSP data analysis, we demonstrate that the same layering can be responsible for a significant TI anisotropy.